Attributional style, self-esteem, and celebrity worship - North, Adrian; Sheridan, Lorraine; Maltby, J.; Gillet, R. (Routledge, 2007)
Two studies were carried out to investigate the relationship between attributional style (Study 1), self-esteem (Study 2), and different forms of celebrity worship. Entertainment social celebrity worship (the most normal form considered) was unrelated to attributional style or self-esteem; intense personal celebrity worship was related positively to self-esteem but also to a propensity toward stable and globalattributions; and borderline pathological celebrity worship (the most negative form considered) was related to external, stable, and global attributions. These results were independent of whether participants were located in Europe or North America, and are discussed in terms of whether celebrity worship should be regarded as positive or negative and as a unitary concept.